Reviews : Hellions of the solar system. (1st February 2019) - Appell, David
Abstract: Comets and asteroids are the fireworks of the solar system. Ancient, mysterious, captivating, they can dazzle the night sky or bring extinctions to life on Earth. In Catching Stardust, Natalie Starkey shares her fascination with these visitors from beyond.